The State Economic Violence And Madurese Women - Khoirul Rosyadi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2022)
This research is a qualitative research that looks at and explores how economic violence perpetrated by the state impacts women. The research was conducted in Bangkalan Madura using a descriptive qualitative approach. The results of the research show that the state policy to increase the price of fuel oil (BBM) is considered as state economic violence. As a result, this country's economic violence has an impact on the lives of Bangkalan Madura women. To get out of this problem, the state should be wiser in raising fuel prices.